A Robust Electrocatalyst for Oxygen Reduction Reaction Assembled with Pt Nanoclusters and a Melem‐Modified Carbon Support. Issue 11 (1st September 2022) - Cheng, Tao; Tan, Xin; Chen, Lifang; Zhao, Xinshu; Kotegawa, Fukue; Huang, Jin; Liu, Yan; Jiang, Hong; Harada, Masafumi; Wang, Yuan
Abstract : Highly active and stable cathode catalysts are crucial functional materials for high‐performance proton exchange membrane fuel cells. Herein, robust cathode catalysts for the oxygen reduction reaction (Pt/melem‐modified carbon (MMC)) that are assembled with Pt nanoclusters (NCs) and MMC supports are reported. The mass activity (MA) of a Pt/MMC catalyst reaches 907 mA mg −1 Pt, which is 3.9 and 4.2 times over a homemade Pt/C catalyst (Pt/VXC‐72R) and a commercial Pt/C catalyst with similar Pt particle sizes, respectively. After 10 000 voltage cycles from 1.0 to 1.5 V at 60 °C, the MA of Pt/MMC decreases by only 2% from the initial value, vastly superior to that of the Pt/C catalysts. Theoretical calculations and X‐ray absorption fine structure analysis results show that chemical bonds form between Pt nanoclusters and MMC. The adsorption energies of OOH* on the catalytic sites in Pt/MMC obviously increase, while those of OH − * decrease compared with those on Pt/C, which accounts for the measured high catalytic activity, providing a promising manner to overcome the specific scaling relations between the stability of adsorbed OH − * and OOH* on a given Pt surface. The high durability of Pt/MMC derives from strong chemical interactions between Pt NCs and the support MMC. Abstract : A prepared melem‐modified carbon‐supported platinum catalyst (Pt/MMC) exhibits high catalytic activity for the oxygen reduction reaction (2.1 times that of the 2020 U.S. Department of Energy target) and excellent durability in an accelerated aging test in a high potential region (1.0–1.5 V). The origin of the obvious promotion effect of MMC on the catalytic properties is clearly revealed for the first time.